Pengaruh Motivasi Dan Persepsi Terhadap Keputusan Berkunjung Wisatawan Di Pulau Onrust - Timorora Sandha Perdhana; Tulus Sukreni (Jurnal Kajian Ilmiah, 2023)
The study aims to determine the influence of Motivation on tourists' Visiting Decisions on Onrust Island, find out the influence of Perceptions on Tourists' Visiting Decisions on Onrust Island and find out the influence of Motivation and Perceptions on tourists' Visiting Decisions on Onrust Island. This research method approach uses quantitative techniques with statistical data to be analyzed through data collection techniques through sample techniques and purposive sampling by involving existing tourists on the island of Onrust. From the sampling data carried out, an analysis was carried out using SPSS. The results showed that both simultaneously and partially, the variables of motivation (X1) and perception (X2) had a significant positive effect on visiting decisions (Y). And based on the results of determination, an R2 value of 0.683 was obtained, which means that motivation and perception influenced the decision to visit by 68.3%.